2011
DOI: 10.14710/jitaa.36.2.77-82
|View full text |Cite
|
Sign up to set email alerts
|

ANALYSIS ON Alu-I GROWTH HORMONE (GHAlu-I) GENE IN BALI CATTLE

Abstract: The research was conducted to identify Alu-I locus of growth hormone (GH) gene in Bali cattle by using 232 blood samples collected from Bali and Lombok islands. PCR-RFLP and sequencing methods were used to detect the polymorphism and nucleotide sequence at Alu-I locus of GH gene. The result showed that Bali cattle from Bali island has one genotype (LL genotype), whereas Bali cattle originating from Lombok island has two genotypes, namely LL and VV genotypes, respectively. The L and V allele frequencies from Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…It meant that the population was still in balance condition according to Hardy-Weinberg equilibrium. In contrary, it was different with the research conducted by Jakaria and Noor (2011). Their result showed that the growth hormone gene in Bali Cattle BPTU only LL which get all genotypes while most of Bali Cattle in Lombok island get genotype LV.…”
Section: Polymorphism Of Myostatin Genesmentioning
confidence: 67%
“…It meant that the population was still in balance condition according to Hardy-Weinberg equilibrium. In contrary, it was different with the research conducted by Jakaria and Noor (2011). Their result showed that the growth hormone gene in Bali Cattle BPTU only LL which get all genotypes while most of Bali Cattle in Lombok island get genotype LV.…”
Section: Polymorphism Of Myostatin Genesmentioning
confidence: 67%
“…Zakizadeh et al (2006) also reported in Iranian cattle. The research of GH gene AluI in Indonesian cattle have been reported in Bali, Madura, and Benggala cattle (Sutarno et al, 2002), West Sumatra Pesisir cattle (Jakaria et al, 2007); Bali cattle (Jakaria & Noor, 2011), but the research of GH gene AluI in exon 5 in Aceh cattle have never been reported. Based on the description above, it is necessary to carry out a research to identify clearly the position of nucleotide changes of DNA sequence on GH gene exon 5 and to identify the number and SNP allele frequency on Aceh cattle.…”
Section: Introductionmentioning
confidence: 99%
“…Musa et al [15] reported that the 2141C variant (Leu) appeared to be monomorphic in all studied animals of Kenana and Butana cattle. The mutation was also not found in Bali cattle [16] .…”
Section: Discussionmentioning
confidence: 77%